2010
DOI: 10.1080/00958971003782608
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, spectroscopic characterization, and in vitro antibacterial studies of a new gold(I) complex with N-acetyl-L-cysteine

Abstract: A new gold(I) complex with N-acetyl-L-cysteine was synthesized and characterized by chemical and spectroscopic techniques. The elemental and thermal analyses of the solid compound fit to the composition AuC 5 H 8 NO 3 S Á 0.75H 2 O. Solid-state 13 C-nuclear magnetic resonance (SSNMR) and infrared (IR) analyses indicate the coordination of the ligand to Au(I) through sulfur. The insolubility of the complex in both polar and non-polar solvents supports a polymeric structure. The antibacterial activity of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
3
12
0
3
Order By: Relevance
“…Pure sodium ibuprofenate did not exhibit antibacterial activity against E. coli, P. aeruginosa and S. aureus in the same experimental conditions. The observed activity of Au(I)-ibuprofen against Grampositive (S. aureus) and Gram-negative microorganisms is similar to the antimicrobial behavior of two phosphine-gold(I) complexes with 2-mercaptopropionic and 6-mercaptonicotinic acids [18] and also of a gold(I) complex with N-acetyl-L-cysteine [6]. Although the mechanism of action of the Au(I)-ibuprofen complex remains uncertain, the observed result warrants further studies concerning the application of the gold(I)-ibuprofen compound as a novel antibacterial agent.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Pure sodium ibuprofenate did not exhibit antibacterial activity against E. coli, P. aeruginosa and S. aureus in the same experimental conditions. The observed activity of Au(I)-ibuprofen against Grampositive (S. aureus) and Gram-negative microorganisms is similar to the antimicrobial behavior of two phosphine-gold(I) complexes with 2-mercaptopropionic and 6-mercaptonicotinic acids [18] and also of a gold(I) complex with N-acetyl-L-cysteine [6]. Although the mechanism of action of the Au(I)-ibuprofen complex remains uncertain, the observed result warrants further studies concerning the application of the gold(I)-ibuprofen compound as a novel antibacterial agent.…”
supporting
confidence: 58%
“…Elsome and coworkers described the antimicrobial activities in vitro and in vivo of a new gold(I)-phosphine complex against Gram-negative bacteria [5]. More recently, new gold(I) and silver(I) complexes with the amino acid N-acetyl-L-cysteine, which show antibacterial activities in vitro against Gram-positive and Gram-negative bacteria, were synthesized in our laboratories [6,7]. Also, a silver(I) complex with acesulfame was evaluated and preliminary biological studies revealed its antimicrobial activity against Mycobacterium tuberculosis as well as against Gram-positive and Gram-negative bacteria [8].…”
mentioning
confidence: 97%
“…Regarding tetrahedral gold(I) complexes, [Au(cis-Ph 2 P(CHvCH)PPh 2 ) 2 ]Cl (35) and [Au(Ph 2 P(CH 2 ) 3 PPh 2 ) 2 ]Cl (36) (Fig. 4b), with chelating diphosphine ligands have been reported to manifest modest activities against Staph.…”
Section: Perspectivementioning
confidence: 99%
“…The majority of research in this area has in fact focussed upon analogues of Auranofin®, i.e. phosphanegold(I) thiolates [24][25][26][27], but with attention also being directed to the study of N-heterocyclic carbene [28], thiolate [29] and carboxylate [30,31] derivatives. Relatively less consideration has been devoted to gold(III) species [32].…”
Section: Introductionmentioning
confidence: 99%